Magic in Islam: By Michael Muhammad Knight (New York: TarcherPerigree, 2016. 246 pages.) (American Journal of Islam and Society, 2016)
What if someone wrote an introduction to Islam that was “not Sunnī-centered,or male-centered, or law-centered” (p. 4)? What if it did not focus on a theoreticalArab Muslim heartland and “let only the classical male theologians andjurists speak” (p. 4)? And what if “magic became the primary lens that informedthe author’s priorities” (p. 4)?Magic in Islam is what would happen. Through “magic,” Knight pokesholes in narratives about Islam held by Muslims (such as the notion of a monolithic,static Islamic orthodoxy) and the general populace (such as the “clashof civilizations” narrative). Title aside, Magic in Islam is really about AmericanIslam, not magic; that is, it implicitly compares Islam’s esoteric heritagewith the dry, hyper-logical brand of Islam popular in American MSAs and atISNA, as well as “Protestant-ish” assumptions about Islam in the broaderAmerican discourse. Knight presents himself as neither a specialist in nor apractitioner of the esoteric, and readers expecting a catalogue of Muslim occultpractices will be disappointed (and perhaps enraged). Instead, he acts as awide-eyed observer guiding the reader through the curiosities of Muslim heritage.Knight did not invent this genre, nor is his main contribution in presentingoriginal research. Rather, his main contribution is in making abstruseacademic texts meaningful to the non-specialist, and in a way that is engagingand fun.From this angle, Magic in Islam is similar to his other projects, such asThe Taqwacores (2004) and Journey to the End of Islam (2009). However,while his writing here is still playfully irreverent, it is considerably toneddown, with only an infrequent swear word or allusion to an indelicate act.Hence, despite its potentially heterodox subject, it is more likely to agreewith conservative sensibilities. Ironically, it is also far more grounded in orthodoxy.While Knight proposes to “let the intro come through marginalizedvoices” (p. 4), particularly loud voices include those of orthodox giantssuch as al-Bukhari and Ahmad ibn Hanbal, as well as less-orthodox but stillmainstream-enough voices such as those of al-Kindi and Ibn al-‘Arabi. (Thisis in contrast to truly marginalized voices, such as those of amulet sellers,jinn exorcists, or women.) Nonetheless, the writing is mature and thoughtful,and I would be comfortable using it as a supplementary textbook in an “Introductionto Islam” class ...